A new method for surveying Purple Heron Ardea purpurea colonies using Google Earth. Issue 3 (3rd July 2021) - Valle, Roberto G.; Baaloudj, Affef; Scarton, Francesco
ABSTRACT: This study describes a new method for counting breeding Purple Herons Ardea purpurea on a large wetland complex (Po Delta, Italy) using Google Earth satellite imagery in comparison to traditional ground counts in 2017. Google Earth counts provide an accurate, rapid, and inexpensive method for estimating the breeding population of Purple Herons, both saving time and increasing count accuracy in comparison to ground counts.